The effect of lean management practices towards operational performance of semiconductor firms in Penang : A case of integrative mechanism (Global Business Management Review (GBMR), 2025)
Introduction: The existing body of literature indicates that lean management is a comprehensive concept, originating from the Toyota Production System, and encompassing various typologies.  This research subsumed all the lean typologies into a holistic model of lean management practices encompassing lean manufacturing concepts and frameworks, lean tools and techniques, and lean activities, as critical dimensions. Similarly, the literature showed that the effect of lean management practices on operational performance was investigated in isolation, with little focus on the impact of intervening variables in this research stream. Drawing supported by System Theory and Resource Based View (RBV), this research investigates the effect of lean management practices on operational performance, with integrative mechanisms as mediating variables, in an entirely new context (Semiconductor firms in Penang, Malaysia). Objectives: The research aimed to empirically investigate the effect of Lean manufacturing concepts and frameworks, Lean tools and techniques, and Lean activities on operational performance. As well, the research aimed to empirically investigate the mediating effect of integrative mechanisms on the relationship between Lean manufacturing concepts and frameworks, Lean tools and techniques, Lean activities, and operational performance.Methods: This study employs a quantitative approach based on a cross-sectional design, focusing on data collection from randomly selected employees of semiconductor firms in Penang through a systematic sampling technique. The primary objective is to examine cause-and-effect relationships between variables. Therefore, the population of the study is 100,000 employees and the sample size is 382 employees. While a well-structured questionnaire was used to collect responses and research data was analyzed using SPSS (statistical package for social sciences) and PLS-SEM (partial least squares-structural equation modeling).Results: The research finding is quite fascinating, the effect of Lean management practices on operational performance and integrative mechanisms has been empirically established. Accordingly, the research finding provided statistical support for the indirect effect of lean management practices on operational performance, through integrative mechanisms. Hence, seven (7) direct and three (3) indirect hypothesized effects were statistically supported.Conclusion: In conclusion, this research accentuated the efficacy of lean management practices as a significant driver of operational performance and integrative mechanisms within organizational settings. The implication is that firms can adopt lean as a tool to integrate internal work processes and achieve operational excellence.